Improvement of Portable Mackintosh Probe Extractor - Wonga@Wanga, Wani; Mohd Zaki, Wan Nazirafazlin; Mohd Ramzam, Muhammad Adzim Ariffi; Kassim, Noraniah (Multidisciplinary Applied Research and Innovation, 2022)
This paper presents a design improvement of the Portable Mackintosh Probe Extractor. This tool was used to pull out the probe rod from the ground after Standard Penetration Test (UPS). UPS is Soil Investigation (SI) technique used in civil engineering as a fundamental step, which is held before any construction activity on site. Previous probe extractor has limitations such as unfriendly to user, large size, weight and not being adjustable, and difficult to store in the vehicle. The improvement design was established and simulated using SolidWorks 2019 software. The parts and assembly in the design process were done to identify the weight and overall size by applying mild steel material properties. Improvements were made by adding an adjustable part on the vertical section, minimize frame thickness to reduce material consumption, and change the holder from slot pin to cylinder to be fit while holding the mackintosh probe. The maximum force of critical area on adjustable vertical and cylinder holder section was identified from stress and equilibrium force calculation. The result is 19.231 kN and 9.615 kN respectively. Finite element analysis (FEA) simulation is conducted on adjustable vertical and cylinder holder section with variable force (2,4,6,8,10,12,14,16,18,20,22) kN and (1,2,3,4,5,6,7,8,9,10,11) kN to identify the profile, graph of force against stress and displacement value. The result of each section was found the displacement change in small value at 5.516×10-3 mm during an increase of 2 kN and 5.411×10-4 mm for each 1 kN increase of force respectively. All graph shows the force directly proportional with stress and displacement. Finally, movement of animation has been run also by this software to determine its functionality in virtual. Based on the results, the improved design of the Mackintosh Probe Extractor can be further to the fabrication stage.